Complete‐Lifecycle‐Available, Lightweight and Flexible Hierarchical Structured Bi2WO6/WO3/PAN Nanofibrous Membrane for X‐Ray Shielding and Photocatalytic Degradation. Issue 7 (24th February 2021) - He, Dayong; Ma, Yuying; Zhao, Rui; Qiu, Ju; Sun, Bolun; Wang, Hao; Yang, Mei; Jia, Xiaoteng; Li, Xiang; Li, Yongxin; Lu, Xiaofeng; Wang, Ce
Abstract: Faced with the presence of radiation sources in many different areas, researchers are beginning to focus on the development of personal protective equipment. The design and manufacture of lightweight, lead‐free, and flexible X‐ray shielding materials have recently become a challenge in materials science, whereas, high‐Z materials, which are essential raw materials for high‐performance X‐ray protective fillers, are non‐renewable, and their exploitation and utilization usually require long‐term planning. In this study, a new route is demonstrated to the preparation of multifunctional polymer/high‐Z material nanofibrous membrane through electrospinning and subsequent solvothermal processes. The resultant Bi2 WO6 /WO3 /polyacrylonitrile hybrid nanofibrous membrane possesses a remarkable X‐ray attenuating property with an attenuation rate of 90.10% at 30 keV and a mass attenuation coefficient of 2.97 cm 2 g −1 at 83 keV. In addition, the freestanding hybrid nanofibrous membrane also possesses excellent photocatalytic activities for the degrading of cationic water pollutants, showing promising potential in industrial wastewater treatment, and providing a new strategy for the design and applications of multifunctional and recyclable shielding materials. Abstract : A typical pre‐designed strategy using the as‐prepared Bi2 WO6 /WO3 /polyacrylonitrile nanofibrous membrane for X‐ray shielding is demonstrated. After the life cycle of the lead‐free X‐ray shielding materials is completed, the nanofibrous membrane can be recycled and used as a photocatalyst in sewage treatment, ensuring that it can continue to create economic benefit and avoid the pollution and waste of nonrenewable high‐Z materials.